Características clínicas y laboratoriales de pacientes adultos ambulatorios con Chikungunya del Hospital Nacional de Itauguá de Paraguay durante la epidemia 2022-2023. - Montiel-Jarolín, Dora; Samudio, Margarita; Torres, Estela; Jarolín, Magalí; Taboada, Verónica; Sánchez, Luis (Medicina Clínica y Social, 2023)
Introduction: Acute infection by chikungunya produces a self-limited infection characterized mainly by high fever, arthralgia, arthritis, headache, myalgia and pruritic rash; a minority presents persistent symptoms that can evolve to chronicity.Objective: to describe the clinical and laboratory characteristics of adult ambulatory patients with chikungunya at a referral hospital during the 2022-2023 epidemic in Paraguay.Materials and Method: descriptive cross-sectional study of adult patients with chikungunya infection who consulted at the Hospital National de Itauguá between January-March 2023.Results: 140 patients between 19 and 79 years old (mean age: 46.6 ± 13.6), 77.9% female and 89.3% from the Central department, were included. 72.9% of the patients were confirmed by RT-PCR and the rest by clinic or serology. 48.6% had some comorbidity, 65% were in the acute phase, and the rest in the subacute phase (35%). The most frequent symptoms were polyarthralgia (96.4%); arthritis (98.6%), fever (95.7%), fatigue (100%), myalgia (96.4%), headache (82.9%), rash (95%). Gastrointestinal symptoms were less frequent such as; nausea (37%), vomiting (15.7%) and diarrhea (20%). Increased C-reactive protein (45.7%), leukopenia (23.6%), increased erythrocyte sedimentation rate (27.9%), and mild hepatic cytolysis (13.6%) were among the main laboratory findings. All patients were treated with paracetamol; 60.4% and 87.8% of the patients in the acute and subacute phase, respectively, received NSAIDs.Conclusion: The combination of high fever and severe arthralgia can be considered the characteristic feature of chikungunya virus infection in this epidemic.
Keywords: Chikungunya- Arthralgia- arbovirus